Co-opting the bacterial lipoprotein pathway for the biosynthesis of lipidated macrocyclic peptides - Jeff Y. Chen; Lingyang Zhu; Kevin Y. Zhang; Deborah A. Berthold; Wilfred A. van der Donk (Proceedings of the National Academy of Sciences, 2026)
Ribosomally synthesized and posttranslationally modified peptides (RiPPs) are structurally diverse natural products that possess a range of bioactivities, often acting as antibiotics, antifungals, or metallophores. In RiPP biosynthesis, different modifying enzymes install an array of chemical motifs onto a precursor peptide. A recently described RiPP-modifying enzyme, ChrH, catalyzes a remarkably complex reaction on its precursor peptide that results in a macrocycle, heterocycle, and S- methyl group. By leveraging comparative genomics, we demonstrate that the products from a subfamily of enzymes related to ChrH display unexpected structural diversity, including the production of unmethylated macrocyclic congeners and C-terminally modified proteins over 30 kDa in size. Several of these precursors contain a signal peptide, sending them for downstream maturation by the bacterial lipoprotein biosynthetic pathway. Like bacterial lipoproteins, such peptides are modified by addition of a diacylglycerol (DAG) group to the N-terminal cysteine residue along with acylation of the N-terminal amine. Genome mining reveals that these RiPP–lipoprotein hybrids, which we term DAG-RiPPs, are widespread across bacterial phyla and are likely involved in different biological roles. Together, these results highlight a maturation paradigm for membrane-bound RiPPs and lay the foundation for the future discovery and bioengineering of other RiPP–lipoprotein hybrids.